Prevalence of Toxoplasma gondii and Toxocara canis among Patients with Uveitis. (April 2015) - Lim, Su Jin; Lee, Sang Eun; Kim, Sun Hyun; Hong, Sung-Hee; You, Yong Sung; Kwon, Oh Woong; Kim, Hyeun Seung
Abstract Purpose: To investigate the prevalence of Toxoplasma gondii and Toxocara canis in patients with uveitis. Methods: Patients with uveitis were examined. Serum antibodies to T. gondii and T. canis were tested by using the enzyme-linked immunosorbent assay. Polymerase chain reaction (PCR) was done using blood and aqueous humor (AH). Results: Ninety-eight patients were enrolled. Mean age was 43.5 ± 13.2 years. Six patients were seropositive for T. gondii with the following pattern: anterior uveitis, 1; posterior uveitis with retinitis, 2; pan uveitis, 2. One patient had a positive PCR result for T. gondii in AH, who showed panuveitis. Twenty-three patients were positive to serum IgG for T. canis with the following clinical manifestation: granuloma, 6; pigmented scar, 3; vitritis, 6—but none were PCR positive. Conclusions: T. gondii and T. canis are still important causes of uveitis. Ocular toxocariasis is not an uncommon cause of uveitis, even in adults.